What's smaller than a pygmy shrew? - Wells, Robert E. (Morton Grove, Ill. : A. Whitman, 1995)
Shows how microscopes are used to see the tiniest parts of the universe. Helps readers understand that the size of any object may be viewed in relation to things smaller and things larger.
Elem. School Library Collection, June 2000.
School Library Journal, May 1995.
Child Study Children's Book Committee, January 1996.
Booklist, January 2004.
The Science Teacher (N.S.T.A.), March 1996.
Elem. School Library Collection.
Keywords: Nuclear size (Physics) -- Juvenile literature; Atoms -- Juvenile literature; Body size -- Juvenile literature; Size perception -- Juvenile literature; Atoms; Size; Atoms; Size; Nuclear size (Physics); Atoms; Body size; Size perception; Size